A theory of strategic uncertainty and cultural diversity - Kets, W; Sandroni, A (Oxford University Press, 2020)
We identify a new mechanism through which cultural diversity affects economic outcomes, based on a model of culture as shared cognition. Under this view, cultural diversity matters because it increases strategic uncertainty. The model can help better understand a variety of disparate evidence, including why homogeneous societies can be more conformist, why diverse societies may get stuck in a low-trust trap, why companies with a strong culture may fail to adopt superior work practices, and why autocratic rulers in diverse societies may overinvest in state capacity.